2021
DOI: 10.3390/nu13020289
|View full text |Cite
|
Sign up to set email alerts
|

Higher Lipopolysaccharide Binding Protein and Chemerin Concentrations Were Associated with Metabolic Syndrome Features in Pediatric Subjects with Abdominal Obesity during a Lifestyle Intervention

Abstract: Background: Elevated circulating plasma levels of both lipopolysaccharide-binding protein (LBP) and chemerin are reported in patients with obesity, but few studies are available on lifestyle intervention programs. We investigated the association of both LBP and chemerin plasma levels with metabolic syndrome (MetS) outcomes in a lifestyle intervention in children and adolescents with abdominal obesity Methods: Twenty-nine patients enrolled in a randomized controlled trial were selected. The lifestyle interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…( 25 ), including nearly one hundred obese children, confirmed that weight loss was associated with a decrease of chemerin levels and improvement of metabolic syndrome parameters such as insulin, HDL-C and TG. The associations between chemerin and weight loss were reported in several studies in obese pediatric and adult population ( 73 77 ). A study by Liu et al.…”
Section: Discussionmentioning
confidence: 83%
“…( 25 ), including nearly one hundred obese children, confirmed that weight loss was associated with a decrease of chemerin levels and improvement of metabolic syndrome parameters such as insulin, HDL-C and TG. The associations between chemerin and weight loss were reported in several studies in obese pediatric and adult population ( 73 77 ). A study by Liu et al.…”
Section: Discussionmentioning
confidence: 83%
“…Reduced body weight has been found to improve intestinal conditions by restoring the selectivity of the intestinal barrier [ 182 , 183 ]. A moderate low-calorie diet together with increased physical activity after 2 and 12 months improved enteral permeability by decreasing chemerin and lipopolysaccharide-binding protein (LBP) levels in adolescents with abdominal obesity [ 184 ]. Assuming that body weight reduction can produce similar results regardless of the method used, metformin has been studied in a group of overweight or obese subjects in the “Survivorship Promotion In Reducing IGF-1 Trial” (SPIRIT) [ 185 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our finding that behavioral weight loss reduces LBP is supported by several lines of evidence. Previous diet- or behavioral-induced weight loss interventions were also found to reduce LBP ( 8 , 14 , 20 ) or intestinal permeability assessed by lactulose:mannitol ratio. ( 13 ) In addition to behavioral weight loss, surgical weight loss has also been shown to reduce LBP, though LBP reduction may depend both on surgical method and timing of LBP measurement post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, weight lost through behavioral intervention or metformin treatment—current first-line treatments for obesity and diabetes, respectively—operate through different physiological mechanisms. ( 19 ) While a behavioral weight loss intervention has been shown to reduce LBP in adolescents with abdominal obesity,( 20 ) there have been no direct comparison between the effects of behavioral weight loss interventions and metformin on LBP in humans.…”
Section: Introductionmentioning
confidence: 99%